2023
DOI: 10.1177/20406207231167050
|View full text |Cite
|
Sign up to set email alerts
|

Brain iron content and cognitive function in patients with β-thalassemia

Abstract: Patients with β-thalassemia (β-TM) may have brain iron overload from long-term blood transfusions, ineffective erythropoiesis, and increased intestinal iron absorption, leading to cognitive impairment. Brain magnetic resonance imaging (MRI) methods such as the transverse relaxation rate, susceptibility-weighted imaging, and quantitative susceptibility mapping can provide quantitative, in vivo measurements of brain iron. This review assessed these MRI methods for brain iron quantification and the measurements f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…A neuroimaging study found that iron content in the brain can be quantified using many MRI techniques, including transverse relaxation rate, susceptibility-weighted imaging, and quantitative susceptibility mapping [46]. Interestingly, serum ferritin levels do not accurately reflect the iron stored in the brain [47].…”
Section: Neurophysiology Of Thalassemia Patients and Its Association ...mentioning
confidence: 99%
“…A neuroimaging study found that iron content in the brain can be quantified using many MRI techniques, including transverse relaxation rate, susceptibility-weighted imaging, and quantitative susceptibility mapping [46]. Interestingly, serum ferritin levels do not accurately reflect the iron stored in the brain [47].…”
Section: Neurophysiology Of Thalassemia Patients and Its Association ...mentioning
confidence: 99%